Microparticle detection to guide platelet management for the reduction of platelet refractoriness in children – A study proposal. Issue 1 (February 2017) - Kanzler, Peter; Mahoney, Andrew; Leitner, Gerda; Witt, Volker; Maurer-Spurej, Elisabeth
Abstract: Microparticles have been shown to shed from a variety of viable cells as a consequence of inflammatory processes, activation or physical stress. Seventy to 90% of circulating microparticles are thought to be platelet-derived. The content of microparticles in blood collected from normal blood donors is highly variable and transfers into the final blood component. Elevated microparticle content (MPC) in donor blood might indicate an asymptomatic clinical condition of the donor which might affect the transfusion recipient, particularly pediatric patients. ThromboLUX is a new technology designed to routinely test biological samples for microparticle content. We compared MPC in platelet-rich plasma (PRP) of apheresis donors and the corresponding INTERCEPT-treated apheresis products (N = 24). The MPCs in donor and product samples were correlated ( r = 0.74, P < 0.001). Microparticles were significantly reduced after plasma replacement and INTERCEPT treatment. These findings are supported by phase contrast microscopy. Platelet transfusions given to patients with fever or systemic inflammation are less efficacious. In addition, transfusing heterogeneous platelets – concentrates with high MPC and activated platelets – to patients whose immune systems are activated might tip them over a threshold and cause platelet refractoriness. Restricting prophylactic platelet transfusions to homogeneous products – concentrates with resting platelets and therefore low MPC – may reduce the risk of refractoriness in cancer patients, especially children with immature immunity. To test this hypothesis we introduce an evaluation protocol for platelet management, i.e ., keeping a split inventory of homogeneous and heterogeneous platelets, and using only homogeneous platelets for prophylaxis as a strategy to reduce refractoriness.